THE EFFECT OF NET PROFIT MARGIN (NPM), RETURN ON ASSETS (ROA), DEBT TO EQUITY RATIO (DER), AND CURRENT RATIO (CR) ON EARNINGS PER SHARE (EPS) IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FROM 2020 TO 2024 - Andrea Dianita; Agustina Widodo (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of net profit margin, return on assets, debt to equity ratio, and current ratio on earnings per share in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The independent variables in this study are net profit margin, return on assets, debt to equity ratio, and current ratio, while the dependent variable is earnings per share. The sampling technique used in this study is purposive sampling, which is a technique for determining samples with specific criteria. The data used in this study is secondary data obtained from the IDX in the form of financial reports of companies listed on the IDX for the period 2020-2024. The results show that the net profit margin variable has a significant positive effect on earnings per share. The return on assets and current ratio variables have a significant negative effect on earnings per share, while the debt to equity variable has an insignificant negative effect on earnings per share in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024.